2008
DOI: 10.1016/j.metabol.2008.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-stimulated release of d-chiro-inositol–containing inositolphosphoglycan mediator correlates with insulin sensitivity in women with polycystic ovary syndrome

Abstract: Some actions of insulin are mediated by inositolphosphoglycan mediators. Deficient release of a putative D-chiro-inositol-containing inositolphosphoglycan (DCI-IPG) mediator may contribute to insulin resistance in women with polycystic ovary syndrome (PCOS). Previously we demonstrated that oral DCI supplementation improved ovulation and metabolic parameters in women with PCOS. However, whether oral DCI mediates an increase in the release of the DCI-IPG mediator and an improvement in insulin sensitivity in wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
83
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 29 publications
12
83
0
8
Order By: Relevance
“…On the other hand, the data shown in our study confirm that rye-buckwheat ginger cakes enhanced with high rutin dosage obtained after dough fermentation may be recognized as DCI-rich product similarly to crackers made of tartary buckwheat flour as described by Yang & Ren [2008]. It should also be pointed out that a much higher dosage of DCI oral supplementation to observe the positive influence on decreasing insulin sensitivity was required to rich a fast-observed effect [Cheang et al, 2008].…”
Section: D-chiro-inositol Contentsupporting
confidence: 82%
See 1 more Smart Citation
“…On the other hand, the data shown in our study confirm that rye-buckwheat ginger cakes enhanced with high rutin dosage obtained after dough fermentation may be recognized as DCI-rich product similarly to crackers made of tartary buckwheat flour as described by Yang & Ren [2008]. It should also be pointed out that a much higher dosage of DCI oral supplementation to observe the positive influence on decreasing insulin sensitivity was required to rich a fast-observed effect [Cheang et al, 2008].…”
Section: D-chiro-inositol Contentsupporting
confidence: 82%
“…Moreover, the important role of DCI glycans as a second messenger in insulin abnormal response was explained by Larner et al [2010]. Medical studies focused on oral DCI administration showed a positive correlation with a decreasing effect on insulin resistance in women with the polycystic ovary syndrome [Cheang et al, 2008;Takahama, et al 2011]. This finding highlighted the importance of food formulated with partial contribution of buckwheat flour that may be useful in diabetes and polycystic ovary syndrome intervention.…”
Section: Introductionmentioning
confidence: 97%
“…In the second pathway, either MYO or its epimerase-converted (39) chiro isoform DCI (44,45) constitutes IPGs (4), which are released from cell membrane glycosylphosphatidylinositols in response to insulin. Once released, IPGs can affect any tissues and cells implicated in insulin action (45), thus potentiating insulin effects (46). The significant reduction of Tyr-P levels in RBC found after MYO treatment and the reduction in insulin AUC confirm that this kind of therapy can improve IR, one of the typical features of PCOS (10).…”
Section: Discussionmentioning
confidence: 92%
“…6 Finally, we noted a significant positive association between change in Matsuda index and change in DCI-IPG released per unit of insulin, as has been demonstrated in our previous study with oral DCI. 8 A major strength of the study is its randomized, doubleblind placebo-controlled design, which provides internal validity to the findings of improved DCI-IPG release per unit of insulin after administering pioglitazone. In addition, these observations are novel since there is no such study in thiazolidinediones, although results are similar to those previously reported for metformin.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Insulin-stimulated release of DCI-IPG mediator correlates with insulin sensitivity in women with PCOS. 8 Furthermore, insulin action is coupled to release of DCI-IPG, an insulinomimetic second messenger that promotes glycogen synthesis. 9 Recently, it was reported that the coupling between insulin action and the release of the DCI-IPG mediator is selectively impaired in PCOS women with obesity this suggests that insulin-stimulated release of the DCI-IPG mediator is defective in obese women with PCOS.…”
Section: Introductionmentioning
confidence: 99%